A Descriptive -Analytical View at the Linguistic Features of the Book Entitled Rotbat Al Hayat Based on the Speech Act Theory - Gholamreza Salemian; Majid Rastande (مطالعات زبانی و بلاغی)
Khaje Yousuf-e Hamedani is a relatively unknown mystic intellectual in the fifth and sixth centuries and his only remaining book is Rotbat Al Hayat. Khaje Yousuf set the book based on questions and answers. In this book, he answers the questions in a hypothetical audience, in simple language, according to the mystical teachings. The text of book is very close to poetry. Undoubtedly, in addition to the element of emotion, in which it is clearly recognizable, its characteristic feature is the music of the word. The author spoke in the book in "The Secret Language." In this interpretation, in addition to paying attention to the mystical delicacy, he also mentions the elegance and beauty of the Persian language and eloquence and rhetoric. In addition to the verbal and spiritual terms, there are some extrinsic factors (the use of non-adjectives, extra combinations, synonyms, total infinitesimals, infinitive, continuity trivial verbs with "simple mania +", prepositions, adjectives, "A" and "and" and "+" but ") and syntactic factors (simple language context, short sentences, vocabulary position, deletion, repetition, queries and turning points) have created a specific song in the prose of the book. In this paper, the linguistic coordinates of this book (with an emphasis on musical elements) have been introduced on the basis of the speech act and discourse analysis.